A vigilância e a repressão política durante o governo Ernesto Geisel (1974-1979): As universidades brasileiras sob a mira da ditadura - Almeida, Dinorah Lopes Rubim (2019)
The thesis brings to light Brazilian Army General Ernesto Beckmann Geisel s government political context (1974-1979), by placing emphasis on political repression and vigilance in Brazilian universities, putting into dialogue the paradox between the politi